Improving city transport with the objective to reduce CO2 emissions - Marjan STERNAD (Transport Problems, 2010)
In the past few years traffic volume is increasing. As a consequence, negative external traffic effects are increasing too, in particular CO2 emissions, which result in global warming and climate changes. CO2 emissions, a by-product of vehicles are much higher in cities due to traffic density. According to European standards, Celje is not a large city; however its traffic poses a great problem that the city authorities will soon be confronted with. This paper focuses on the city centre of Celje, where traffic flow was measured and CO2 emissions calculated. Using alternative solutions the aim was to present impacts on the environment in the municipality of Celje in an event of changed traffic regimes. In order to reach the guidelines of sustainable transport development in the municipality of Celje, in the future, different measures for reducing negative external effects of city transport will have to be put into force, for only this way the quality of city life can be improved and compatibility of environmental, economic and social objectives provided.